Basic Writers in Composition's Public Turn: Voice and Influence in the Basic Writing Classroom - Minnix, Christopher (Journal of Basic Writing, 2015)
While basic writing has made a public turn by incorporating service learning and community literacy pedagogies, basic writers are not often discussed in the vast and growing research on public writing in composition studies. Scholarship on public writing in composition has produced important discussions of the outcomes of public writing pedagogy, but the "incomes" of public writing—the experiences, cultural and linguistic differences, and knowledge of and dispositions towards public life—that students bring to public writing classrooms have gone largely unexplored. Scholars and teachers of basic writing can productively challenge public writing pedagogy to attend to these incomes by expanding their research on socioeconomic and cultural difference and access to students' writing in the public realm. I develop this argument out of current educational research on youth and civic engagement, beginning with a discussion of what Meira Levinson has called the "civic empowerment gap" among poor and minority students. largue that the literacy narrative is a genre that provides students with rich opportunities to explore and negotiate the "incomes" they bring to public writing, as well as a genre that can be utilized and adapted for public persuasion.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80NDI4MDEwMA